Beyond the bounds of the dogmatic image of thought: the development of critical, creative thinking in the mental health professions. Issue 4 (20th June 2013) - Roberts, M.
<x xml:space="preserve">Abstract</x> Accessible summary Reflections upon what it might mean to think, and about what inherited presuppositions or images might influence what thinking is thought to consist of, are not readily considered in the mental health care literature. However, the work of the 20th century French philosopher Gilles Deleuze and, in particular, his account of 'the dogmatic image of thought' can be employed to illustrate how such considerations can be of relevance to the theoretical and practical concerns of mental health professionals. In doing so, Deleuze's work can be understood as seeking to sensitize mental health professionals to the dangers of unreflectively adopting a restrictive notion of what it means to think, as well as an exhortation to develop critical, creative thinking in the mental health professions that moves beyond the bounds of the traditional, dogmatic image of thought. Abstract Considerations about what it might mean to think, and about what inherited presuppositions determine what thinking is thought to consist of, are not readily reflected upon in the mental health care literature. However, this paper will propose that such considerations are of relevance to, and possess important implications for, the mental health professions, and it will do so within the context of the work of the 20th century philosopher Gilles Deleuze. In particular, the paper will provide an accessible exposition of what Deleuze refers to as the 'dogmatic image of thought', along with an examination of his suggestion that this traditional image, and its associated presuppositions, not only determine what is considered to be the ostensible 'nature' of thought, but also delineate what the activity of thinking ought to be concerned with. Moreover, it will be argued that Deleuze's exposition and critique of the image of thought can be understood as seeking to sensitize mental health professionals to the dangers of unreflectively perpetuating a restrictive notion of what it means to think, as well as being an exhortation to develop critical, creative thinking in the mental health professions that moves beyond the bounds of that traditional, dogmatic image of thought.